Optimization of a dip coating process used for the production on a 2 photocatalytic film deposited on a polymeric substrate (2023)
This work was a collaborative study between the Universidad de los Andes and the University of Malta. It investigated the effect of process parameters on the deposition of photocatalytic films on a PMMA substrate using a Dip Coating method and how these affect coverage, coating thickness and photocatalytic efficiency. At the end of the investigation it was concluded that, the concept of producing photocatalytic coatings using a dipping coating technique is very attractive because it combines the possibility of low cost and fast processing. However, the simultaneous use of PMMA and chloroform seems to be an unfortunate combination. Firstly, because pH adjustment of the colloidal solution is to say the least difficult and secondly because leaching of polymer components generates more contaminants than the photocatalytic reaction manages to destroy. The search for a more suitable precursor must therefore continue.